Recent Patents on Alphavirus Protein Expression and Vector Production - Aranda, Alejandro; Ruiz-Guillen, Marta; I. Quetglas, Jose; Bezunartea, Jaione; Casales, Erkuden; Smerdou, Cristian (Recent Patents on Biotechnology, 2011)
Alphaviruses contain a single-strand RNA genome that can be modified to express heterologous genes at high levels. Alphavirus vectors can be packaged within viral particles (VPs) or used as DNA/RNA layered systems. The broad tropism and high expression levels of alphavirus vectors have made them very attractive for applications like recombinant protein expression, vaccination or gene therapy. Expression mediated by alphavirus vectors is generally transient due to induction of apoptosis. However, during the last years several non-cytopathic mutations have been identified within the replicase sequence of different alphaviruses, allowing prolonged protein expression in culture cells. Some of these mutants, which have been patented, have allowed the generation of stable cell lines able to express recombinant proteins for extended periods of time in a constitutive or inducible manner. Production of alphavirus VPs usually requires cotransfection of cells with vector and helper RNAs providing viral structural proteins in trans. During this process full-length wild type (wt) genomes can be generated through recombination between different RNAs. Several new strategies to reduce wt virus generation during packaging, optimize VP production, increase packaging capacity, and provide VPs with specific targeting have been recently patented. Finally, hybrid vectors between alphavirus and other types of viruses have led to a number of patents with applications in vaccination, cancer therapy or retrovirus production.
Keywords: vector production